if (-3)⁴ × (-3)⁶=(-3)? then ?=
Answers
Answered by
0
(-3)⁴*(-3)6=(-3)10
using a raise to m * a raise to n= a raise to m+ n.
Answered by
0
Answer:
GIVEN :-
(-3)⁴ × (-3)⁶=(-3)?
TO FIND :-
?
PROOF
a^n x a^m = a^m+n
= (-3)⁴ × (-3)⁶ = (-3)^4 + 6
= (-3)^10
thus ? = 10
Step-by-step explanation:
hope this helps you pls mark me as brainliest
correct me if i made a mistake
Similar questions
Computer Science,
2 months ago
Environmental Sciences,
2 months ago
Biology,
2 months ago
Hindi,
3 months ago
Accountancy,
3 months ago
English,
11 months ago